From Regulation to Consumer Safety: Unpacking the Legal Dimensions of ”˜Share-in-Jar’ Cosmetic Sales - Shalmont, Jerry; Hartanto, Gabriela Zefanya (Law Review, 2023)
Repackaging products in share-in-jar is a process of dividing the contents of a product from its original size into several smaller containers. Such products are popular amongst consumers who are looking for product samples to try on before buying the actual product that tends to be costly. However, several business actors are selling share-in-jar products that do not conform with the applicable law, namely by failing to comply with the sanitary and hygiene requirements during the repackaging process and not providing detailed product information, therefore, resulting in consumer losses. In light of this, a controversy arose concerning legal protection for consumers who suffer losses as a result of the sale of cosmetics in share-in-jar and the legal liability of business actors for the losses incurred by consumers who use share in jar cosmetics. The objective of this research is to look into the consumer protection policies that develop as a result of violations of the Indonesian Law, as well as the legal culpability of business actors for infringing on consumers' rights while buying and selling cosmetics.